The evidence for natural therapeutics as potential anti-scarring agents in burn-related scarring. Issue 1 (4th May 2016) - Mehta, M.; Branford, O. A.; Rolfe, K. J.
Abstract: Though survival rate following severe thermal injuries has improved, the incidence and treatment of scarring have not improved at the same speed. This review discusses the formation of scars and in particular the formation of hypertrophic scars. Further, though there is as yet no gold standard treatment for the prevention or treatment of scarring, a brief overview is included. A number of natural therapeutics have shown beneficial effects both in vivo and in vitro with the potential of becoming clinical therapeutics in the future. These natural therapeutics include both plant-based products such as resveratrol, quercetin and epigallocatechin gallate as examples and includes the non-plant-based therapeutic honey. The review also includes potential mechanism of action for the therapeutics, any recorded adverse events and current administration of the therapeutics used. This review discusses a number of potential 'treatments' that may reduce or even prevent scarring particularly hypertrophic scarring, which is associated with thermal injuries without compromising wound repair.